Brain inflammation induces post-synaptic changes during early synapse formation in adult-born hippocampal neurons. - Chugh, Deepti; Nilsson, Per; Afjei, Seyedeh Atiyeh; Bakochi, Anahita ; 0000-0001-8144-8525; Ekdahl Clementson, Christine (Experimental Neurology, 2013)
An inflammatory reaction in the brain is primarily characterized by activation of parenchymal microglial cells. Microglia regulate several aspects of adult neurogenesis, i.e. the continuous production of new neurons in the adult brain. Hippocampal neurogenesis is thought to be important for memory formation, but its role in brain diseases is not clear. We have previously shown that brain inflammation modulates the functional integration of newly formed hippocampal neurons. Here, we explored whether there is a defined time period during synaptic development when new neurons are susceptible to brain inflammation. Newly formed hippocampal neurons, born in an intact environment in the adult mouse brain, were exposed to lipopolysaccharide (LPS)-induced inflammation during either early or late phases of excitatory and inhibitory synaptogenesis. We used intra-hippocampal injections of GFP-retroviral vector (RV-GFP) to label the new neurons and ipsilateral LPS injection at either 1 or 4weeks post-RV-GFP injection. A single intra-hippocampal LPS injection induced an inflammatory response for at least 3weeks, including an acute transient pro-inflammatory cytokine release as well as a sub-acute and sustained change in microglial morphology. The general cytoarchitecture of the hippocampal dentate gyrus, including granule cell layer (GCL) volume, and astrocytic glial fibrillary acidic protein expression was not different compared to vehicle controls, and no Fluoro-Jade-positive cell death was observed. New neurons encountering this inflammatory environment exhibited no changes in their gross morphology. However, when inflammation occurred during early stages of synapse formation, we found a region-specific increase in the number of thin dendritic spines and post-synaptic density-95 (PSD-95) cluster formation on spines, suggesting an enhanced excitatory synaptic connectivity in the newborn neurons. No changes were observed in the expression of N-cadherin, an adhesion molecule primarily associated with excitatory synapses. At the inhibitory synapses, alterations due to inflammation were also evident during early but not later stages of synaptic development. Gephyrin, an inhibitory scaffolding protein, was down-regulated in the somatic region, while the adhesion molecules neuroligin-2 (NL-2) and neurofascin were increased in the somatic region and/or on the dendrites. The GABAA receptor-α2 subunit (GABAAR-α2) was increased, while pre/peri-synaptic GABA clustering remained unaltered. The disproportional changes in post-synaptic adhesion molecules and GABAA receptor compared to scaffolding protein expression at the inhibitory synapses during brain inflammation are likely to cause an imbalance in GABAergic transmission. These changes were specific for the newborn neurons and were not observed when estimating the overall expression of gephyrin, NL-2, and GABAAR-α2 in the hippocampal GCL. The expression of interleukin-1-type 1 receptor (IL-1R1) on preferentially the somatic region of new neurons, often in close apposition to NL-2 clusters, may indicate a direct interaction between brain inflammation and synaptic proteins on newborn neurons. In summary, this study provides evidence that adult-born hippocampal neurons alter their inhibitory and excitatory synaptic integration when encountering an LPS-induced brain inflammation during the initial stages of synapse formation. Changes at this critical developmental period are likely to interfere with the physiological functions of new neurons within the hippocampus.